Adverse event surveillance in small animal anaesthesia: an intervention‐based, voluntary reporting audit. (19th October 2015) - McMillan, Matthew; Darcy, Hannah
Abstract: Objective: To develop, test and refine an 'intervention‐based' system for the surveillance of adverse events (AEs) during small animal anaesthesia. Study design: Prospective, voluntary reporting audit. Animals: A total of 1386 consecutive small animal anaesthetics (including 972 dogs and 387 cats). Methods: Adverse events were defined as undesirable perianaesthetic events requiring remedial intervention to prevent or limit patient morbidity. Using previous reports, 11 common AEs were selected and 'intervention‐based' definitions were devised. A voluntary reporting audit was performed over 1 year at a university teaching hospital. Data on AEs were collected via paper checkbox forms completed after each anaesthetic and were assimilated using an electronic database. Interventions were performed entirely at the discretion of the attending anaesthetist. Comparisons between dogs and cats were made using Fisher's exact tests. Results: Forms were completed for 1114 anaesthetics (a compliance of 80.4%), with 1001 AEs reported in 572 patients. The relative frequency of AEs reported were as follows: arousal or breakthrough pain (14.9%), hypoventilation (13.5%), hypotension (10.3%), arrhythmias (5.8%), hyperthermia/hypothermia (5.0%), airway complications (4.8%), recovery excitation (4.6%), aspiration risk (4.5%), desaturation (2.8%), hypertension (1.7%) and 'other' (3.7%). Canine anaesthetics (57.3%) were more likely to involve AEs than were feline anaesthetics (35.5%, p < 0.01). Escalation in postanaesthetic care was required in 20% of cases where an AE was reported (8% of anaesthetics overall). In 6% of cases (2% overall), this involved management in an intensive care unit. There were six intra‐anaesthetic fatalities (0.43%) during this period. The tool was widely accepted, being considered quick and easy to complete, but several semantic, logistical and personnel factors were encountered. Conclusions and clinical relevance: Simple intervention‐based surveillance tools can be easily integrated into small animal anaesthetic practice, providing a valuable evidence base for anaesthetists. A number of considerations must be addressed to ensure compliance and the quality of data collected.